Rethinking the Rejuvenation Pathway: Rural Digital Nomadism as an Exploratory Strategy Amidst Bali’s Overtourism Pressures - Situmorang, Fransisco (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Overtourism threatens destination sustainability, accelerating stagnation or decline within the Tourism Area Life Cycle (TALC), as Bali’s ecological stress, cultural commodification, and governance fragility illustrate. This study explores rural digital nomadism as an exploratory strategy for sustainable rejuvenation in Kelecung Eco Village, Tabanan, Bali. Using a longitudinal single-case design (2020-2026), it draws on 22 interviews, focus group discussions, participant observation, and a feasibility survey of 85 respondents. Integrating co-living, co-working, and authentic cultural experiences initially extended visitor stays, diversified household income, and repositioned the village within global flows. Constrained by weak marketing, livingwage pressures, and institutional resistance, the village strategically refocused on its edu-ecotourism model while keeping rural digital nomadism as its main future direction. Theoretically, the study extends TALC to the Global South through participatory nomadism, distinguishing community-embedded models from urban nomad bubbles. Practically, it shows that rejuvenation depends on formal institutional and financial support.